176k views
2 votes
What is the reason for each step in the solution of the equation 4x - 1 = -2(x+1)

2 Answers

3 votes
Answer:-1/6

Step by step explanation:

4x - 1 = 2(x+1)

Move the terms

4x-1 = -2x -2

Collect the like terms

4x + 2x = -2+1

Calculate the terms

6x = -1

Divide both sides by 6

X= -1/6
User Patros
by
6.1k points
2 votes

Answer:

it's because we understand the concept easily

Explanation:

4x-1= -2(x+1)

or, 4x-1= -2x+(-2)

or, 4x-1= -2x-2

or, 4x+2x= -2+1

or, 6x= -1

or, x= -1/6

User Estephany
by
6.4k points